2015
DOI: 10.1016/j.cell.2015.05.053
|View full text |Cite|
|
Sign up to set email alerts
|

A Synergistic Interaction between Chk1- and MK2 Inhibitors in KRAS-Mutant Cancer

Abstract: KRAS is one of the most frequently mutated oncogenes in human cancer. Despite substantial efforts, no clinically applicable strategy has yet been developed to effectively treat KRAS-mutant tumors. Here, we perform a cell-line-based screen and identify strong synergistic interactions between cell-cycle checkpoint-abrogating Chk1- and MK2 inhibitors, specifically in KRAS- and BRAF-driven cells. Mechanistically, we show that KRAS-mutant cancer displays intrinsic genotoxic stress, leading to tonic Chk1- and MK2 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 15 publications
0
55
0
Order By: Relevance
“…While KRAS is clearly a potent oncogenic driver, additional genomic aberrations may exist in KRAS-driven lung adenocarcinomas that could impact the therapeutic response. For instance, KRAS mutations were recently shown to cocluster with mutations affecting the p53 response in lung adenocarcinoma (6). These data suggest that an impaired DNA damage response maybe selected in KRASmutant lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…While KRAS is clearly a potent oncogenic driver, additional genomic aberrations may exist in KRAS-driven lung adenocarcinomas that could impact the therapeutic response. For instance, KRAS mutations were recently shown to cocluster with mutations affecting the p53 response in lung adenocarcinoma (6). These data suggest that an impaired DNA damage response maybe selected in KRASmutant lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 84%
“…Intratracheal administration of adenoviral Cre recombinase (Adeno-Cre) leads to the expression of oncogenic Kras G12D from its endogenous locus. In addition to this simple Kras-driven model, we also used Kras LSL.G12D/wt ; Tp53 fl/fl mice, in which both Tp53 alleles are flanked by LoxP sites (6,28,31). In these compound-mutant mice, Adeno-Cre drives expression of Kras G12D and simultaneous deletion of both Tp53 alleles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, both SMYD2 (Xu et al 2015) and MAPKAPK3 (Wysk et al 1999) have been linked to IL-6 and TNFα regulation. MAPKAPK3 and its closely related family member, MAPKAPK2 (which is not methylated by SMYD2), have also been implicated in DNA damage response and chemotherapy response (Morandell et al 2013;Dietlein et al 2015), and their common substrate, HSP27, has been shown to mediate the effects of gemcitabine toxicity in PDAC cells (Mori-Iwamoto et al 2007;Kuramitsu et al 2012). These observations and our data showing greater effects of chemotherapy upon inhibition of SMYD2 in PDAC cells raise the possibility that SMYD2 inhibitors and MAPKAPK2/3 inhibitors may be used in combination to enhance the effects of chemotherapy in PDAC patients.…”
Section: Discussionmentioning
confidence: 99%